(untitled) (International Journal of Statistics in Medical Research, 2015)
Introduction: Libya is a North African country classified under the Eastern Mediterranean Regional Office. In response to the general paucity of literature regarding cancer in Libya, this study aims to analyze various risk factors for breast cancer among patients in Benghazi, Libya. Material and Methods: Using records from a major primary oncology clinic, data was gathered from breast cancer patients. A total of 301 patients were diagnosed with breast cancer in the study period. For the purpose of risk factor determination, this hospital-based case control study consisted of 212 recently diagnosed cases of breast cancer attending the oncology clinic at Al-Jamhouria hospital in Benghazi. Age matched controls (n=219) were randomly enrolled from other medical departments of Al-Jamhouria hospital and the general population visiting the hospital. Chi square was used to assess significance of the risk factors and the corresponding odds ratio (O.R.) and 95% CI were calculated to assess the magnitude of associations. Results: A total of 1478 cases presented to the gynecological oncology clinic at Al-Jamhouria hospital during the period of 2007-2008. Of these cases, around 20% (n=301) were breast cancer patients. The average age of presentation was 49 years + S.D 13 years, with most of the cases (61%, n=184) being premenopausal. Over 90% (n=273) of breast cancer patients are diagnosed at stage II or later. More than 16% of cases seek medical attention when the malignancy has already reached stage IV. Diabetes, hypertension and family history of other malignancies were found to significantly increase the risk of developing breast cancer. Discussions: A range of socioeconomic risk factors were also analyzed (i.e. parity, breastfeeding etc…) and some were found to be protective. Libyan breast cancer cases are slightly older compared to the rest of the Arab world, but are younger than their counterparts in the West. The major issue in the Libyan scenario is delayed presentation which significantly worsens the prognosis. Hence, all the recommendations focus on increased awareness, the implementation of a national cancer control plan and a national screening program and training healthcare professions in palliative care